2010
DOI: 10.1038/nsmb.1889
|View full text |Cite
|
Sign up to set email alerts
|

A paralog of lysyl-tRNA synthetase aminoacylates a conserved lysine residue in translation elongation factor P

Abstract: Aminoacyl-tRNA synthetase (aaRS) paralogs with unknown functions exist in various species. We now report novel 'protein lysylation' by an Escherichia coli lysyl-tRNA synthetase paralog, GenX/PoxA/YjeA. X-ray crystallographic analysis shows that the structure of the GenX protein resembles that of a class II aaRS. Further in vitro studies reveal that it specifically aminoacylates EF-P with lysine. The shape of the protein substrate mimics that of the L-shaped tRNA, and its lysylation site corresponds to the tRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
164
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(175 citation statements)
references
References 59 publications
10
164
0
1
Order By: Relevance
“…Notably, the modification of EF-P occurs at a lysyl residue (lysine 34) that corresponds to the same position as the lysyl residue that is converted to hypusine in aIF5A and eIF5A. Two other laboratories have independently corroborated aspects of these findings (6,60). YjeK belongs to the family of 2,3-lysine aminomutases, ironsulfur cluster-containing enzymes that catalyze the interconversion of L-lysine and 3,6-diaminohexanoic acid (also known as ␤-lysine) (8).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Notably, the modification of EF-P occurs at a lysyl residue (lysine 34) that corresponds to the same position as the lysyl residue that is converted to hypusine in aIF5A and eIF5A. Two other laboratories have independently corroborated aspects of these findings (6,60). YjeK belongs to the family of 2,3-lysine aminomutases, ironsulfur cluster-containing enzymes that catalyze the interconversion of L-lysine and 3,6-diaminohexanoic acid (also known as ␤-lysine) (8).…”
supporting
confidence: 64%
“…While PoxA bears close homology to the catalytic domain of the class II lysyl-tRNA synthetase (LysRS) family of enzymes that catalyze the addition of lysine to its cognate tRNA Lys , a number of studies have failed to show that PoxA can aminoacylate a tRNA (1,36,37). PoxA instead catalyzes the ligation of (R)-␤-lysine to the side chain of the conserved lysyl residue in EF-P to yield an unusual lysyl-␤-lysine moiety (42,48,60). Salmonella poxA and yjeK mutants display nearly identical phenotypes, including increased resistance to S-nitrosoglutathione (GSNO) and hypersusceptibility to a large number of unrelated antimicrobial compounds (7,42,55).…”
mentioning
confidence: 99%
“…However, two recent studies also indicated that EF-P could act during elongation by facilitating the synthesis of proteins containing stretches of consecutive proline residues (5,6). EF-P is similar in size and shape to a tRNA and can be post-translationally modified by a lysyl-tRNA synthetase paralog, PoxA (7,8). In a reaction analogous to tRNA aminoacylation, PoxA activates (R)-␤-lysine and subsequently transfers it to a conserved residue (Lys-34) in EF-P (9).…”
mentioning
confidence: 99%
“…In bacteria, the translational arrest is relieved by the translation elongation factor P (EF-P), which binds to the stalled ribosomes and stimulates peptide bond formation (5,6). In Escherichia coli, EF-P is posttranslationally modified by YjeA, YjeK, and YfcM (EpmA, EpmB, and EpmC) (8)(9)(10) and the resulting lysinylation modification has been shown to be critical for the rescue activity of EF-P in vivo and in vitro (5,6). EF-P homologs exist in all archaea and eukaryotes, termed aIF-5A and eIF-5A, respectively (11).…”
mentioning
confidence: 99%